Sexting e divulgação não consensual de imagens intimas na adolescência: inovações metodológicas e processos de resiliência - Muniz, Haryadny Kamylla Macedo (Universidade Federal de São Carlos, 2022)
The expression sexting is used to denote activities that involve sending text messages, images and videos with sexual content and/or intimate images. Although the practice of sexting is a contemporary expression of sexuality and does not represent, a priori, a risk factor for the development of adolescents, there are risk factors associated with its practice. The exposure of intimate images in a non-consensual way appears as one that brings suffering to the lives of children, who are mostly women. As it is a dangerous phenomenon, images of intimate exhibition complexes with teenagers can be delivered. This occurs, between the difficulties of access for the victims and the possibility of re-victimization of the adolescents, which can be verified on the coerced with research teams. Based on these findings, this dissertation was organized into two articles. In Article 1, we study how adolescents are themes presented in a collection of com, especially in data studies that involve sensitive data, a research modality that involves the collection of adolescents in digital format. In important hypotheses, it is known that as video platforms, teenagers were allowed to share their stories in the way they felt most appropriate and convenient. Some of the teenagers were informed this time for the first time that they had addressed the matter publicly. The fact that teenagers have the opportunity to edit the videos is also relevant, as it allows them to reflect on the content they produce and share what they really want, exercising a leading role. Also, by recording the videos in spaces they choose and feel, they enable spontaneity and authenticity, the fundamental requirements in research. In Article 2, we sought to analyze protective factors and nearby resilience processes in adolescents who had images released in a non-consensual manner. For this, videos of teenagers residing in Brazil and the United States were selected who had their intimate images released without consent and who voluntarily published their reports on an online video platform. This was a qualitative, exploratory-descriptive case study, based on a multiple study. After defining the reports of teenagers presented on the YouTube platform, 15 videos were selected, 9 videos with reports of teenagers in the United States and 6 videos of residents in the United States and 6 videos of residents in Brazil. Data was analyzed using computer techniques. 3 topics were reported in Article 2, namely: (i) Interfaces between and protection; (ii) “This made me who I am”: Resilience Processes experienced by adolescents; (iii) ‘No face, no story’: Protagonism and Harm Reduction Recommendations. Both articles are released and disseminated for the scientific advancement produced in the area.
Sexting and non-consensual disclosure of Intimate images in adolescence: methodological innovations and resilience processes
Keywords: Sexting; Adolescência; Divulgação não consensual; Violência; Resiliência; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO